2018
DOI: 10.3390/en11040773
|View full text |Cite
|
Sign up to set email alerts
|

Exergo-Ecological Assessment of Waste to Energy Plants Supported by Solar Energy

Abstract: Hybridization of Waste to Energy (WtE) plants with solar facilities can take competing energy technologies and make them complementary. However, realizing the benefits of the solar integration requires careful consideration of its efficiency. To analyse such systems from the point of view of resource efficiency, the pure energy analysis is not sufficient since the quality of particular energy carriers is not evaluated. This work applies the exergo-ecological analysis using the concepts of thermoecological cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The overall system was simulated by varying the superheated steam parameters (pressure and temperature). In a very preliminary evaluation (Mendecka et al 2018) a parametric analysis varying both pressure and temperature of the steam superheated in the solar section was carried out. In this work, we assume three different steam parameters values (couples of pressure and temperature), for the integrated system, representative of the previously investigated ranges, which are: 51 bar and 440 °C; 60 bar and 480 °C and 70 bar and 520 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The overall system was simulated by varying the superheated steam parameters (pressure and temperature). In a very preliminary evaluation (Mendecka et al 2018) a parametric analysis varying both pressure and temperature of the steam superheated in the solar section was carried out. In this work, we assume three different steam parameters values (couples of pressure and temperature), for the integrated system, representative of the previously investigated ranges, which are: 51 bar and 440 °C; 60 bar and 480 °C and 70 bar and 520 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Bianchi et al [29] investigated the WTE systems coupled with gas combined cycles, and results demonstrated that the hybrid system could obtain higher net power efficiency and economic benefits than the separate system. A combination of a WTE plant and solar energy facilities was studied, using solar energy to attain external superheating and achieving a 4.5% net efficiency enhancement [30]. Chen et al [31] combined a WTEU and a CFPU, upgrading total power efficiency and getting economic profits.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning system integration, Consonni et al [25] and Poma et al [26] discussed a hybrid WtE-gas turbine combined cycle scheme, where the steam yielded from the WtE boiler is further heated by the gas turbine exhaust gas and then enters into the steam turbine for power production. Mendecka et al [27] presented a novel WtE design incorporated with a concentrating solar power system, in which the solar energy is harvested to superheat the live steam of the WtE boiler. Chen et al [28] explored the integration of a WtE plant and a coal-fired power plant by feeding the heat acquired from the incineration into the steam cycle of the coal power section.…”
Section: Introductionmentioning
confidence: 99%